Pengetahuan remaja perempuan terkait vaksinasi human papillomavirus (HPV) - Novie Nurlatifah; Yanti Hermayanti; Witdiawati Witdiawati; Ida Maryati; Nina Sumarni (Holistik Jurnal Kesehatan, 2026)
Background: Knowledge of adolescent girls regarding Human Papillomavirus (HPV) vaccination plays an important role in preventing cervical cancer. Lack of knowledge may reduce awareness and participation in vaccination programs. HPV vaccination is an effective preventive measure; therefore, early understanding is essential. Adolescent girls are the primary target, as the optimal age for vaccination is 9–14 years. Purpose: To describe the level of knowledge of adolescent girls regarding HPV vaccination. Method: This study used a descriptive quantitative cross-sectional design with total sampling, involving 73 respondents who were willing to participate. The instrument was a validated HPV vaccination knowledge questionnaire (31 valid items; r > 0.361) with reliability (Cronbach’s alpha = 0.932). Data were analyzed descriptively using percentages. Results: Most respondents had moderate knowledge (63%), followed by good (27.4%) and poor (9.6%). In each category, some respondents had not received the HPV vaccine, including those with good and moderate knowledge. Respondents generally understood aspects of cervical cancer prevention, benefits of HPV vaccination, administration methods, and side effects. However, knowledge was still limited regarding early symptoms of cervical cancer, asymptomatic HPV infection, antibody formation and duration, and vaccine dosage. Conclusion: Uneven knowledge levels indicate the need for improved health education to enhance adolescents’ understanding of and participation in HPV vaccination.      Keywords: Adolescent Girls; Human Papillomavirus Vaccination; Knowledge.